2013
DOI: 10.1017/s104161021300118x
|View full text |Cite
|
Sign up to set email alerts
|

Program evaluation of a telepsychiatry service for older adults connecting a university-affiliated geriatric center to a rural psychogeriatric outreach service in Northwest Ontario, Canada

Abstract: The program was rated as being highly valued across all modalities of evaluation. Members of the referring team believe that access to a geriatric psychiatrist has broadened the team's knowledge base, its use of assessment tools, and increased their ability to better construct their patients' treatment plans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 9 publications
5
49
0
Order By: Relevance
“…In Canada, a programme evaluation of a telepsychiatry service for older adults indicated that HCPs expressed generally positive and satisfactory perceptions of the use of the technology (Conn et al . ). The telepsychiatry service had been in place since 2002 to deliver psychiatry consultations to residents in northern remote communities of Ontario.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In Canada, a programme evaluation of a telepsychiatry service for older adults indicated that HCPs expressed generally positive and satisfactory perceptions of the use of the technology (Conn et al . ). The telepsychiatry service had been in place since 2002 to deliver psychiatry consultations to residents in northern remote communities of Ontario.…”
Section: Resultsmentioning
confidence: 97%
“…As the JBI has no specific tool to assess programme evaluation study, Conn et al . () were not assigned to the level of evidence. For details, refer to the last column of Table .…”
Section: Resultsmentioning
confidence: 99%
“…Research that has used telepsychiatry for older populations has found it to be viewed positively by clinicians, nursing home staff, families, and patients, and to lead to improvements in mental health status. 23,78 Concern about the acceptability of technology among older adults may deter individuals from pursuing videoconferencing-based programs, but research has found that older adults often find the technology to be satisfactory, with almost two-thirds reporting no preference between face-to-face and video-based interactions. 85 Thus, the use of telepsychiatry in elderly populations would be a valuable area for future research.…”
Section: Discussionmentioning
confidence: 99%
“…One Canadian demonstration project connecting older adults with a university-related psychogeriatric service improved the referring team's knowledge base and subsequent ability to construct better treatment plans for patients [8]. In Australia, one statewide health department has demonstrated that telehealth can successfully provide emergency mental health care for rural communities [9].…”
Section: Introductionmentioning
confidence: 99%